The native and naturalised species of Peltocalathos and Ranunculus (Ranunculaceae: Ranunculeae) in southern Africa - Manning, J.C.; Goldblatt, Peter (African Biodiversity & Conservation, 2013)
The five native and naturalised species of Ranunculus L. and Peltocalathos Tamaru (Ranunculaceae: Ranunculeae) fromsouthern Africa are reviewed, with full descriptions and nomenclature, taxonomic history, ecological notes, and distributiondata. All species are illustrated. Peltocalathos, a monotypic genus based on R. baurii MacOwan, has been overlooked in theregional literature until now. The new name R. dregei J.C.Manning & Goldblatt is proposed as a replacement name for thelater homonym R. meyeri Harv., non Lowe. We conclude that the poorly known R. capensis Thunb. represents juvenile formsof the widespread and variable R. multifidus Forssk. and we synonymise the name, along with the three trivial epithets R.pinnatus var. hermannii DC., R. pubescens var. glabrescens Burtt Davy and R. pubescens var. harveyanus Burtt Davy, whichhave been overlooked in the recent literature. Based on number (mostly < 40 achenes per head) and size (mostly 1.2–1.8 mmlong) of achenes, we conclude that the southern African material of the aquatic species recently re-identified as R. rionii Laggeris more appropriately treated as R. trichophyllus Chaix.